The IL-20RB receptor and the IL-20 signaling pathway in regulating host defense in oral mucosal candidiasis - Beute, John E.; Kim, Alex Y.; Park, Jamie J.; Yang, Allen; Torres-Shafer, Keshia; Mullins, David W.; Sundstrom, Paula (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomembranous candidiasis (thrush), erythematous candidiasis, and fungal esophagitis are infections of the barrier mucosa of the upper gastrointestinal tract. The majority of these infections are caused by Candida albicans, an opportunistic fungal pathogen that frequently exists as a harmless commensal on mucosal surfaces lining the gastrointestinal tract. Oral infections are initiated in the superficial stratified squamous epithelium, in which keratinocytes are the most abundant host cells and are the initial points of contact with C. albicans present in saliva. Intrinsic features of oral keratinocytes are likely to play important roles in host defense and tissue homeostasis in oral candidiasis. One understudied pathway that may be important for modulating oral candidiasis is the IL-20 cytokine signaling pathway that employs keratinocyte IL-20RB receptors as ligands for IL-19, IL-20, and IL-24. We report that production of human oral keratinocyte il24 mRNA and protein are stimulated during co-culture with C. albicans. To test the role of the IL-20 family signaling pathway in oral candidiasis, Il20rb-/- mice (lacking the IL-20RB receptor) were compared to wild-type mice in a murine model of oropharyngeal candidiasis. Fungal burdens and percent loss in body weight were determined. Despite comparable fungal burdens, the Il20rb-/- mice exhibited less weight loss over the course of their infection compared to the B6 mice, suggestive of reduced overall disease consequences in the mutant mice. Interference with IL-20 family cytokine signaling may be useful for augmenting the ability of the host to defend itself against pathogens.